Growth differentiation factor-15 in heart failure: new update of clinical relevance - Berezin, A. E.; Poliasnyi, V.; Kovalevskaya, L. A.; Berezin, A. A.; Березін, Олександр Євгенійович (My University, 2021)
Heart failure (HF) remains a leading cause of mortality in patients with overt cardiovascular disease (CVD). New Universal Definition and Classification of HF is supposed to use biomarker strategy based on measure of circulating (mainly natriuretic peptides and high-sensitive cardiac troponins) and genetic indicators to identify patients at higher risk of HF and choose optimal strategy to diagnose and treat. Although the first-generation biomarkers (natriuretic peptides, high sensitive cardiac troponins) are widely used, the second-generation biomarkers of fibrosis and inflammation may have additional promising benefit in clear assessment of adverse cardiac remodeling and providing differentiation between several subtypes of HF. Growth differential factor-15 (GDF15) is a stress-induced multifactorial cytokine, which belong to the transforming growth factor beta superfamily. GDF15 is markedly expressed in various cells and involved in glucose and energy homoeostasis, regulation of appetite, and body weight loss. GDF15 influences tissue protection from ischemia / reperfusion, and oxidative stress damage. The aim of the narrative review is to elucidate the diagnostic and therapeutic role of GDF15 in HF. We found that GDF-15 is a promising indicator of poor clinical outcomes and predictor of HF, and it could be a powerful component of a multiple biomarker strategy in managing HF patients.
Keywords: Heart failure; biomarkers; growth differential factor-15; prediction; outcomes